Examining ELT-knowledge-based learning outcomes within the national curriculum guidelines of Indonesian Islamic tertiary education - Sukirman Sukirman; Caroline Teresa Linse (Studies in English Language and Education, 2024)
The study aims to critically analyse the clarity, observability, and measurability of ELT knowledge-based learning outcomes (LOs) as outlined in the current national curriculum guidelines for Indonesian Islamic higher education institutions. The researchers employed document analysis to assess 22 items of the LOs within the guidelines published in 2018 by the Ministry of Religious Affairs (MoRA) through the Directorate of Indonesian Islamic Higher Education. Then, the researchers applied the Blooms revised taxonomy as the theoretical framework, converting LOs illustrative verbs to Blooms illustrative verbs to examine the quality of LOs to determine whether the LOs promote higher- or lower-order thinking skills. This study shows that a significant majority (95.45%) of the analysed LOs in the current national guidelines suffer from poor design (unclear, unobservable, and unmeasurable) due to the absence of Blooms cognitive illustrative verbs. Collectively, these findings have important implications for educators and policymakers to pay more attention to the quality of their designed LOs. It suggests an urgent need for the Directorate of Indonesian Islamic Higher Education to revise its LOs because they risk affecting the quality, relevance, and effectiveness of their education in generating graduates who have global competitiveness. Poorly designed LOs promote only lower-order skills, which paralyse graduates global competitiveness because they do not possess the knowledge required in the international arena. It is hoped that this study will serve as an inspiration to other countries and educational authorities facing similar challenges, encouraging them to be more meticulous in crafting well-designed LOs.